PENERAPAN LAYANAN BIMBINGAN DAN KONSELING PADA ANAK USIA DINI DI TAMAN KANAK-KANAK KOTA SAMARINDA - Pratiwi, Yuni Ika; Tunru, Andi Alif; Fariska, Dea (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Guidance and counseling services in early childhood education play an important role in supporting children’s social, emotional, behavioral, and self-adjustment development. However, the implementation of guidance and counseling services at the kindergarten level still faces several challenges, including the absence of professional counselors, limited teacher understanding regarding guidance and counseling services, and the lack of structured counseling programs. In addition, studies concerning the implementation of guidance and counseling services in local contexts, particularly in kindergartens in Samarinda, remain limited, as previous studies have primarily focused on conceptual discussions and program development. This condition indicates a research gap related to the actual implementation of guidance and counseling services for early childhood education in kindergarten settings. This study aimed to describe the implementation of guidance and counseling services for early childhood children in kindergartens in Samarinda City. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of kindergarten principals and teachers selected using purposive sampling techniques. Data were collected through observations, interviews, and documentation, while data analysis was conducted using the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of guidance and counseling services for early childhood children in kindergartens in Samarinda City had been integrated into learning activities and daily habituation programs. The services implemented included orientation services, information services, social and emotional development assistance, simple individual counseling, and collaboration with parents. Teachers served as facilitators, mentors, developmental observers, mediators, and liaisons between schools and parents. Nevertheless, the implementation still encountered several obstacles, such as limited teacher competencies, the absence of structured guidance and counseling programs, and the lack of professional counselors. This study concludes that guidance and counseling services in kindergartens in Samarinda City have been implemented through preventive and developmental approaches; however, their implementation still requires strengthening through the development of structured counseling programs and the enhancement of teacher competencies to optimize service delivery